2005
DOI: 10.1002/jbt.20092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cholinephosphotransferase activity in lung injury induced by 2-chloroethyl ethyl sulfide, a mustard analog

Abstract: Exposure to mustard gas causes inflammatory lung diseases including acute respiratory distress syndrome (ARDS). A defect in the lung surfactant system has been implicated as a cause of ARDS. A major component of lung surfactant is dipalmitoyl phosphatidylcholine (DPPC) and the major pathway for its synthesis is the cytidine diphosphocholine (CDP-choline) pathway. It is not known whether the ARDS induced by mustard gas is mediated by its direct effects on some of the enzymes in the CDP-choline pathway. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…We found that SM exposure resulted in a time-dependent decrease in native SP-D expression in bronchiolar epithelial cells which was directly correlated with inflammation and tissue injury. These results are consistent with reports that mustards damage type II cells and alter the surface tension of BAL, and suggest a potential mechanism leading to the development of acute respiratory distress syndrome in SM-exposed individuals (van Helden et al, 2004; Sinha Roy et al, 2005; Mukhopadhyay et al, 2008). Interestingly, SP-D staining increased in alveolar macrophages following SM exposure which was likely due to uptake of the protein by these phagocytic cells.…”
Section: Discussionsupporting
confidence: 92%
“…We found that SM exposure resulted in a time-dependent decrease in native SP-D expression in bronchiolar epithelial cells which was directly correlated with inflammation and tissue injury. These results are consistent with reports that mustards damage type II cells and alter the surface tension of BAL, and suggest a potential mechanism leading to the development of acute respiratory distress syndrome in SM-exposed individuals (van Helden et al, 2004; Sinha Roy et al, 2005; Mukhopadhyay et al, 2008). Interestingly, SP-D staining increased in alveolar macrophages following SM exposure which was likely due to uptake of the protein by these phagocytic cells.…”
Section: Discussionsupporting
confidence: 92%
“…The two forms of CPT are localized in ER/microsomes and mitochondria in the fetal lung and type II epithelial cells that differ by their substrate specificity based on preference for unsaturated or saturated DAGs, K m values, and sensitivity to inhibitors [89, 90]. CPT levels appear also to be regulated at the level of protein stability [91] and by inhibitory lipids such as ceramides [90, 92]. CPT activity is upregulated just prior to birth, decreasing in the adult lung [93].…”
Section: Synthesis and Regulation Of Surfactant Phospholipidsmentioning
confidence: 99%